Combined Effect of Synthetic and Natural Polymers in Preparation of Cetirizine Hydrochloride Oral Disintegrating Tablets: Optimization by Central Composite Design. (5th January 2017) - Patro, Chandra Sekhar; Sahu, Prafulla Kumar
Abstract : Our aim was to employ experimental design to formulate and optimize cetirizine hydrochloride oral disintegrating tablets (ODTs) by direct compression technique, using the mutual effect of synthetic croscarmellose sodium (CCS) and natural Hibiscus rosa-sinensis mucilage (HRM) as disintegrants in the formulation. Central composite design (CCD) was applied to optimize the influence of three levels each of CCS (X 1 ) and HRM (X 2 ) concentrations (independent variables) for investigated responses: disintegration time (DT) (Y 1 ), % friability (F ) (Y 2 ), and % cumulative drug release (DR) (Y 3 ) (dependent variables). This face-centered second-order model's reliability was verified by the probability and adequate precision values from the analysis of variance, while the significant factor effects influencing the studied responses were identified using multiple linear regression analysis. Perturbation and response surface plots were interpreted to evaluate the responses' sensitivity towards the variables. During optimization, the concentrations of the processed factors were evaluated, and the resulting values were in good agreement with predicted estimates endorsing the validity. Spectral study by Fourier Transform Infrared Spectroscopy (FTIR) and thermograms from Differential Scanning Calorimetry (DSC) demonstrated the drug-excipients compatibility of the optimized formulation. The optimized formulation has concentrations of 9.05 mg and 16.04 mg of CCS and HRM each, respectively, and the model predicted DT of 13.271 sec, F of 0.498, and DR of 99.768%.